2007
DOI: 10.1042/cs20060265
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome proteolytic activity in skeletal muscle is increased in patients with sepsis

Abstract: Patients with sepsis in the ICU (intensive care unit) are characterized by skeletal muscle wasting. This leads to muscle dysfunction that also influences the respiratory capacity, resulting in prolonged mechanical ventilation. Catabolic conditions are associated with a general activation of the ubiquitin-proteasome pathway in skeletal muscle. The aim of the present study was to measure the proteasome proteolytic activity in both respiratory and leg muscles from ICU patients with sepsis and, in addition, to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 34 publications
(39 reference statements)
6
69
0
3
Order By: Relevance
“…More recently, increased activity of the proteasome and direct evidence for increased muscle proteolysis have been shown in both respiratory (30% increase compared with controls) and limb (45-55% increase compared with controls) muscle of septic patients in the ICU [35].…”
Section: Upregulation Of Muscle Protein Breakdown In Icuawmentioning
confidence: 99%
“…More recently, increased activity of the proteasome and direct evidence for increased muscle proteolysis have been shown in both respiratory (30% increase compared with controls) and limb (45-55% increase compared with controls) muscle of septic patients in the ICU [35].…”
Section: Upregulation Of Muscle Protein Breakdown In Icuawmentioning
confidence: 99%
“…der kalziumabhängi-gen Calpaine kommt [55,69,121]. Dabei ist es vermutlich das Ziel dieser katabolen Vorgänge, dem Organismus vermehrt freie Aminosäuren zur Verfügung zu stellen, um den gesteigerten Bedarf zu decken.…”
Section: > Die Cim Tritt Häufiger Und Früher Auf Als Die Cipunclassified
“…Experimental and human studies have clearly demonstrated that proteasome activities increase in wasting condition such as cancer (Bossola et al 2003), burns (Chai et al 2002), sepsis (Klaude et al 2007), chronic obstructive pulmonary disease (Ottenheijm et al 2006), chronic renal failure (Raj et al 2003), congestive heart failure (Filippatos et al 2005), as well as in disuse or denervation atrophy (Kandarian and Stevenson 2002).…”
Section: Introductionmentioning
confidence: 98%